Perbandingan Jumlah Bakteri pada Sedimen Mangrove di Ekosistem Mangrove Rehabilitasi dan Alami di Desa Perancak, Jembrana, Bali - Ni Putu Wira Argiantini; Ima Yudha Perwira; Ni Made Ernawati (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2021)
This study aimed to know the difference of total bacterial number on the sediment of rehabilitation and natural mangrove ecosystem in the Desa Perancak, Jembrana, Bali. Sediment sampling was carried out in November 2019. The sediment sampling was carried out at two different sites, 3 station from the rehabilitation mangrove zone and 3 station from natural mengrove zone. Total bacterial number in the sediment was enumerated using Total Plate Count Method, pH was measured using pH meter, and dissolved solid was measured using TDS meter. The result showed that there was no bog difference in the bacterial amount between rehabilitation and natural mangrove ecosystem. The total dissolved solid in the rehabilitation mangrove was higher than that in the natural mangrove. The pH of sediment in the rehabilitation mangrove was lower than that in the natural mangrove. This result indicate that there is difference in the species community in both mangrove ecosystems.